Growth and Employment in the Dominican Republic : Options for a Job-Rich Growth - Abdullaev, Umidjon; Estevao, Marcello (Washington, D.C. : International Monetary Fund, 2013)
The Dominican Republic has posted high rates of output and productivity growth, but labor market indicators have remained weak during the past 20 years. This paper documents these trends, showing that the rapid productivity growth originates in a few sectors, while the bulk of job creation is concentrated elsewhere. The speed of job creation has not been enough to raise employment rates, and lackluster real earnings along with still-rampant labor market informality suggest that most of the new jobs are of low quality. Low real wages and low labor force participation suggest the need of raising market wages above fallback incomes to attract individuals to the labor force. For that, measures to improve education and reduce product market distortions would be helpful.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet